Fossilization and an emerging social dialect - MacDonald, Marguerite G. (Lenguas Modernas, 2017)
In an evolving ethnic community, both fossilization and social dialect may influence the variety of the host language spoken by the community members. The present article examines this phenomenon in the English of the second generation in the Cuban- American community of Little Havana, located in Miami, Florida. While fossilization is usually associated with adult acquisition, this study finds that even if English is acquired before adolescence, there can be psycholinguistic as well as sociocultural motivation for linguistic variation. The phonological variation appears to have both these sources. Subjects who were five or older when they began the acquisition of English appear to exhibit fossilization in their phonology. However, nonphonological variation is primarily the result of sociocultural factors